Tourism in the Los Lagos Region: experiences of the Mapuce people and reflections in the context of the pandemic (Huellas, 2021)
This article deals with the development of tourism in Los Lagos region (Neu-quén Province) and inquiries about the experiences of the Mapuce people in the north, center and south of the aforementioned region. In the context of the COVID-19 pandemic, the question that guides the work is: In which order of priority were Mapuce communities that provide tourist services in these territories placed? This work aims at identifying the socioeconomic condition in the tourist territories of Los Lagos Region and in the Mapuce communities that carry out this activity in the context of the COVID-19 pandemic. The work starts from recognizing the history of exclusion, marginality and social inequality of the Mapuce people resulting from public policies, territorial configuration and productive activities promoted by the State and its role in the recent development of autonomous initiatives related to tourism. A qualitative methodology is used on the basis of secondary information and field work in the territory.
Keywords: Los Lagos region; tourism; Mapuce people; inequality; pandemic